Entre se dizer e ser dito criança: significados e sentidos construídos pelas crianças acerca da ação de participação - Melo, Lis Albuquerque (2012)
This study aimed to understand the significances and meanings constructed by children regarding the action of participation. From the many places that children occupy in Brazilian society, it appears that, among the discourses and social practices that enhance their right to participation and voice in social and political life, consistent with the fact that rights and duties are assigned to the children, it coexists those that claim a place of inadequacy and inferiority in the course of development of the rational subject of an eminently adultocentric society. From a historical-cultural perspective of the human constitution, it is understood that children are constructed as such by the context characteristics tensions. Participation in this study is understood as an action that is realized in the interaction with the other (s) in cultural and social contexts filled with values, focusing on everyday situations, with their diversity of possible ways to participate. This qualitative research was developed with a group of children and adolescents aged between 7 and 17 years, participants in a social project in northeastern Brazil. As techniques for generating data, we used the methodology of the Workshops, characterizing an intervention research, and participant observation. The registers adopted were the field diary and video recording of meetings, followed by transcription. The constructed data was analyzed from the reference of Network of Significations and the microgenetic analysis by the historical-cultural matrix. The children and the adolescents created participatory strategies to deal with the tension between the instituted and the experience, producing meanings around shared hegemonic significances about their participation. Thus, the participation of these subjects happens in their daily lives, on most simple interaction, in micro-spaces of relations, as participatory practices socially recognized for this process to take place. However, images of children present in practices with children often end up formatting the experience of being a child and to participate, disregarding the contexts, needs and possibilities of a time that is always being undone, redone and built.